Activated mGluR5 protects BV2 cells against OGD/R induced cytotoxicity by modulating BDNF-TrkB pathway. (27th July 2017) - Ye, Xinchun; Yu, Lu; Zuo, Dandan; Zhang, Liang; Zu, Jie; Hu, Jinxia; Tang, Jiao; Bao, Lei; Cui, Chengcheng; Zhang, Ruixue; Jin, Guoliang; Zan, Kun; et al.
Highlights: The protective effects of activated mGluR5 against OGD/R induced cytotoxicity in BV2 cells is proposed. Blockade of BDNF/TrkB pathway partly abrogated the protective effects of activated mGluR5. BDNF/TrkB pathway may be involved in regulating the protective effects of activated mGluR5. Abstract: Activated Metabotropic glutamate receptors 5(mGluR5) exhibits protective effects against ischemic brain damage, but the underlying mechanisms are not clearly known. Brain-derived neurotrophic factor (BDNF), as a valuable member of neurotrophic factor family, exerts its protection by combining with its high-affinity receptor tyrosine protein kinase B (TrkB). To investigate the role of activated mGluR5 against oxygen-glucose deprivation (OGD)/reoxygenation (R)-mediated cytotoxicity, the cell viability, apoptosis, the release of inflammatory cytokines and accumulation of reactive oxygen species (ROS) were evaluated in BV2 cells (Microglia cell line) with or without OGD/R exposure. Our data show that CHPG (the selective mGluR5 agonist) pretreatment, as an mGluR5 agonist, protected BV2 cells against OGD/R-induced cytotoxicity, apoptosis, the release of inflammatory cytokines, and the accumulation of ROS. However, these effects were significantly reversed by the mGluR5 antagonist MPEP pretreatment. Our data also show that the expressions of BDNF and TrkB were significantly decreased in BV2 cells with OGD/R exposure. CHPG pretreatment significantly enhanced the expressions of BDNF and TrkB in BV2 cells with OGD/R exposure. However, the increased expressions were significantly abrogated by MPEP pretreatment. In addition, inhibition of BDNF/TrKB pathway by K252a also attenuated the protective effects of activated mGluR5 against OGD/R-induced cytotoxicity, apoptosis and the release of inflammatory cytokines. Morever, pretreatment with exogenous BDNF protected BV2 cells against OGD/R induced apoptosis and release of inflammatory cytokines. These data suggested that BDNF/TrKB pathway may be involved in regulating activated mGluR5′ protective effects against OGD/R induced cytotoxicity in BV2 cells.